2017
DOI: 10.1161/circinterventions.116.004801
|View full text |Cite
|
Sign up to set email alerts
|

Serial Assessment of Strut Coverage of Biodegradable Polymer Drug-Eluting Stent at 1, 2, and 3 Months After Stent Implantation by Optical Frequency Domain Imaging

Abstract: URL: https://www.clinicaltrials.gov. Unique identifier: NCT01844843.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 29 publications
(16 reference statements)
0
16
0
1
Order By: Relevance
“…Table 1 summarises the data collected from the included studies. Ten of the 20 studies were randomised control trials (RCT) [ 22 , 23 , 28 , 29 , 32 34 , 37 , 39 , 40 ], five were cohort studies [ 25 , 27 , 31 , 36 , 38 ], two were retrospective autopsy studies [ 26 , 35 ], and three were prospective, single-arm trials [ 22 , 24 , 30 ]. Four studies looked at BMS, with one comparing two BMS with varying strut thickness [ 39 ], and three comparing the effects of BMS and DES on ISR rates [ 29 , 32 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarises the data collected from the included studies. Ten of the 20 studies were randomised control trials (RCT) [ 22 , 23 , 28 , 29 , 32 34 , 37 , 39 , 40 ], five were cohort studies [ 25 , 27 , 31 , 36 , 38 ], two were retrospective autopsy studies [ 26 , 35 ], and three were prospective, single-arm trials [ 22 , 24 , 30 ]. Four studies looked at BMS, with one comparing two BMS with varying strut thickness [ 39 ], and three comparing the effects of BMS and DES on ISR rates [ 29 , 32 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies looked at BMS, with one comparing two BMS with varying strut thickness [ 39 ], and three comparing the effects of BMS and DES on ISR rates [ 29 , 32 , 37 ]. Six studies investigated BRS [ 21 , 22 , 24 , 25 , 27 , 38 ], and 19 out of the 20 included studies investigated at least one drug-eluting stent. There were missing data for the scaffold and polymer types used for some studies as well as strut thickness.…”
Section: Resultsmentioning
confidence: 99%
“…The present study demonstrated the comparable coverage percent between BP-DES and DP-DES, which was in line with the previous reports. At 3-month follow-up, the Ultimaster™ BP-DES and the Synergy™ BP-DES achieved similar strut coverage percent of 95.2% and 94.5%, respectively [2,10,11], while the Xience™ DP-DES and the Resolute™ DP-DES also showed the coverage percent of 94.5% and 93.8%, respectively [12,13]. Both previous and the present studies showed comparable neointimal coverage percent after implantation of the contemporary BP-and DP-DESs assessed by OCT.…”
Section: Strut Coverage In the Bp-and The Dp-desmentioning
confidence: 90%
“…3summarizes the results of OCT analysis. Light intensity of superficial neointima in the BP-DES group was lower than that in the DP-DES group (120 2. [102.9, 154.8] vs. 170.9 [117.6, 227.4], p < 0.001), whereas deep neointima in the BP-DES showed comparable to that in the DP-DES.…”
mentioning
confidence: 86%
See 1 more Smart Citation